Digital Trends in Language and Literature: Asia and the 21st century - Mohamed Salleh, Rabiah Tul Adawiyah; Di Biase, Bruno (International Islamic University Malaysia, 2021)
GUEST EDITORS' COLUMN Introduction to the special issue